Cholesterol suppresses antimicrobial effect of statins - Mohammad Reza Haeri; Kenneth White; Mohammad Qharebeglou; Malek Moein Ansar (Iranian Journal of Basic Medical Sciences, 2015)
Objective(s):Isoprenoid biosynthesis is a key metabolic pathway to produce a wide variety of biomolecules such as cholesterol and carotenoids, which target cell membranes. On the other hand, it has been reported that statins known as inhibitors of isoprenoid biosynthesis and cholesterol lowering agents, may have a direct antimicrobial effect on the some bacteria. The exact action of statins in microbial metabolism is not clearly understood. It is possible that statins inhibit synthesis or utilization of some sterol precursor necessary for bacterial membrane integrity. Accordingly, this study was designed in order to examine if statins inhibit the production of a compound, which can be used in the membrane, and whether cholesterol would replace it and rescue bacteria from toxic effects of statins. Materials and Methods: To examine the possibility we assessed antibacterial effect of statins with different classes; lovastatin, simvastatin, and atorvastatin, alone and in combination with cholesterol on two Gram-positive (Staphylococcus aureus and Enterococcus faecalis) and two Gram-negative (Pseudomonas aeruginosa and Escherichia coli) bacteria using gel diffusion assay. Results: Our results showed that all of the statins except for lovastatin had significant antibacterial property in S. aureus, E. coli, and Enter. faecalis. Surprisingly, cholesterol nullified the antimicrobial action of effective statins in statin-sensitive bacteria. Conclusion: It is concluded that statins may deprive bacteria from a metabolite responsible for membrane stability, which is effectively substituted by cholesterol.